Atypical audio-visual speech perception and McGurk effects in children with specific language impairment - Leybaert, Jacqueline; Macchi, Lucie; Huyse, Aurélie; Champoux, François; Bayard, Clémence; Colin, Cécile; Berthommier, Frédéric (Frontiers in Psychology, 2014)
Audiovisual speech perception of children with Specific Language Impairment (SLI) and children with Typical Language Development (TLD) was compared in two experiments using /aCa/ syllables presented in the context of a masking release paradigm. Children had to repeat syllables presented in auditory alone, visual alone (speechreading), audiovisual congruent and incongruent (McGurk) conditions. Stimuli were masked by either stationary or amplitude modulated noise. Although children with SLI were less accurate in auditory and audiovisual speech perception, they showed similar auditory masking release effect than children with TLD. Children with SLI also had less correct responses in speechreading than children with TLD, indicating impairment in phonemic processing of visual speech information. In response to McGurk stimuli, children with TLD showed more fusions in AM noise than in ST noise, a consequence of the auditory masking release effect and of the influence of visual information. Children with SLI did not show this effect systematically, suggesting they were less influenced by visual speech. However, when the visual cues were easily identified, the profile of responses to McGurk stimuli was similar in both groups, suggesting that children with SLI do not suffer from an impairment of audiovisual integration. An analysis of percent of information transmitted revealed a deficit in the children with SLI, particularly for the place of articulation feature. Taken together, the data support the hypothesis of an intact peripheral processing of auditory speech information, coupled with a supra modal deficit of phonemic categorization in children with SLI. Clinical implications are discussed.